Anacreontic motifs in Maksym Rylskyi's poetry - Науменко, Наталя (Видавничо-поліграфічний центр “Київський університет”, 2025)
The author of this article analyzed the 'wine-imaged' poems by Maksym Rylskyi, written in different years, having based on the esthetic concepts of the anacreontic style. Dated back to the early period, these were the folk song stylizations ('White snow, red wine...'), philosophical meditations ('I've just taken a sip from my glass...'), sonnets related to intimate lyrics ('Once in warm days of vintage...'); whereas in the 1950s the generic palette of Rylskyi's 'wine' poetry got complemented with lyrical portraits ('A Winegrower,' 'Roses and Grapes'). This method allowed confirming M. Rylskyi's lyrics as the base for Ukrainian 'khamriyyat,' or the specific poetic massif connected with images of wine drinking and tasting, feasts, and love. The importance of researching the poetic heritage under this angle is defined as revelation and interpretation of archetypal imagery through the details of everyday life.

У статті на основі естетичних концепцій анакреонтичного стилю в поезії проаналізовано вірші Максима Рильського різних років, засновані на образності вина. У ранньому періоді творчості такими були стилізації народних пісень ("Білий сніг, вино червоне..."), філософські медитації ("Я тільки надпив свою чарку..."), сонети-взірці інтимної лірики ("У теплі дні збирання винограду..."), а вже у 1950-х роках жанрову палітру "винної" поезії доповнили ліричні портрети ("Виноградар", "Троянди й виноград"). Відтак утверджено, що саме лірику М. Рильського можна визначити основою для формування українського "хамрійяту", тобто специфічного масиву поезії, пов'язаного з мотивами винопиття, застілля, кохання. Важливість дослідження поетичного доробку в цьому ключі полягає у виявленні та інтерпретації архетипної образності через деталі повсякденного життя.
Анакреотичні мотиви у ліриці Максима Рильського
Keywords: the 20th century Ukrainian literature; M. Rylskyi's works; poetry; wine; imagery; anacreontics; українська література ХХ століття; творчість М. Рильського; поезія; вино; образність; анакреонтика